Fabrication of graphene nanoplatelets/MgAl-layered double hydroxide nanocomposites as efficient support for gold nanoparticles and their catalytic performance in 4-nitrophenol reduction - Tom Dunlop (Process Safety and Environmental Protection, 2023)
The catalytic reduction of 4-nitrophenol is of considerable importance to a multitude of applications and industries. The present work introduces a new catalyst (AuNP/GNP/MgAl-LDH) containing gold nanoparticles (AuNP) supported on graphene nanoplatelets (GNP) intercalated in Mg Al layered double hydroxides (MgAl-LDH) for the reduction of 4-nitrophenol to 4-aminophenol using NaBH4 as a reducing agent. The catalyst was characterized by FTIR, XRD, STEM, TEM, and BET specific surface area. The XRD analysis showed the presence of crystalline phases of gold on the supports, while TEM demonstrated that MgAl-LDH provided uniform binding sites for AuNPs and prevented agglomeration. Similar reaction rate constant was determined for the disappearance of 4-nitrophenol and for the appearance of 4-aminophenol. The reaction rate constant was the highest for AuNP/GNP/MgAl-LDH, followed by AuNP/MgAl-LDH and AuNP/GNP. AuNP/GNP/MgAl-LDH was found stable after five repeated cycles.